Multicentre clinical simulation evaluation of the ISO 80369‐6 neuraxial non‐Luer connector1. (21st February 2019) - Cook, T. M.; Wilkes, A.; Bickford Smith, P.; Dorn, L.; Stacey, M.; Kinsella, S. M.; Sharpe, P.; Phillips, P.
Summary: To avoid potentially fatal wrong‐route neuraxial drug errors, international standard ISO 80369‐6 specifying a non‐Luer neuraxial connector design was published in 2016. We describe usability studies used in development of the design. Thirty‐eight doctors and 17 nurses performed simulated procedures on manikins, using devices fitted with Luer connectors or draft ISO 80369‐6 'non‐Luer' connectors. The procedures included spinal anaesthesia; intrathecal chemotherapy; lumbar puncture, cerebrospinal fluid collection and pressure measurement; epidural catheter placement with bolus injection and critical care use. Participants attempted cross connection between neuraxial connectors and a range of other medical device connectors, including those from the ISO 80369 small‐bore connector series. Video recording analysis was used for all assessments. Participants subjectively assessed performance of the draft non‐Luer connector, including suitability for routine clinical use. Participants performed 198 procedures. The connector achieved easy, leak‐free connections. The willingness of participants to use the non‐Luer connectors were: spinal anaesthesia 100%; intrathecal chemotherapy 88%; lumbar puncture, cerebrospinal fluid collection and pressure measurement 93%; epidural catheter placement with bolus injection 78%; critical care use 100%. Concerns raised were generally device related, rather than connector related. Most cross‐connection attempts failed, even using above clinical forces and, when successful, were judged of low clinical risk potential; the exception was a malaligned connection between the non‐Luer slip and female Luer connectors. This led to revision of the dimensional tolerances of the non‐Luer connector to reduce this risk, before publication of the final specification in 2016. We conclude that the ISO 80369‐6 neuraxial non‐Luer connector is suitable for clinical use.